2017
DOI: 10.1186/s13756-017-0289-6
|View full text |Cite
|
Sign up to set email alerts
|

Urinary pathogenic bacterial profile, antibiogram of isolates and associated risk factors among pregnant women in Ambo town, Central Ethiopia: a cross-sectional study

Abstract: BackgroundUrinary tract infection (UTI) is a well-known bacterial infection posing serious health problem in pregnant women. A study was conducted in pregnant women with the objectives of estimating prevalence of UTI, determining antibiogram of the bacterial isolates and assessment of the potential risk factors associated with UTI.MethodsA cross-sectional study design was used to collect 300 mid-stream urine samples from pregnant women from March 2016 to December, 2016. Samples were inoculated into Cysteine La… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
59
1
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 58 publications
(81 citation statements)
references
References 38 publications
17
59
1
4
Order By: Relevance
“…Highest prevalence of ASB uropathogens was observed in the age range of 26-31 years for both pregnant and nonpregnant women and the mean ages of 23.3±5.2 and 24.2±5.6 years were stipulated for pregnant and non-pregnant women respectively in this study, which was similar to that reported in Hawassa referral hospital [12], Ambo town [16] Gondar tertiary teaching hospital [6] in Ethiopian cities, Benin city [1,39], Ibadan [33] and University of Uyo teaching hospital, Nigeria [4]. The increased prevalence observed within this age range may be attributed to multiparity which has been documented as one of the risk factors for ASB in pregnant women in many populations [4,[15][16][17]44). This is in tandem with the result of this present study.…”
Section: Discussionsupporting
confidence: 86%
See 4 more Smart Citations
“…Highest prevalence of ASB uropathogens was observed in the age range of 26-31 years for both pregnant and nonpregnant women and the mean ages of 23.3±5.2 and 24.2±5.6 years were stipulated for pregnant and non-pregnant women respectively in this study, which was similar to that reported in Hawassa referral hospital [12], Ambo town [16] Gondar tertiary teaching hospital [6] in Ethiopian cities, Benin city [1,39], Ibadan [33] and University of Uyo teaching hospital, Nigeria [4]. The increased prevalence observed within this age range may be attributed to multiparity which has been documented as one of the risk factors for ASB in pregnant women in many populations [4,[15][16][17]44). This is in tandem with the result of this present study.…”
Section: Discussionsupporting
confidence: 86%
“…In this present study conducted at Anua, Offot Ukwa district, the highest rate of ASB uropathogens was observed in the third trimester pregnancy, which is in harmony with other researches [1,12,16,20] in Ibadan, Ethiopia and Sri Lanka but disagrees with others [4,6] that reported highest prevalence in the first trimester and second trimester pregnancy. Several anatomical and hormonal changes in pregnancy lead to urethral dilation and urinary stasis which contributed to increased risk of developing urinary tract infection [2,45].…”
Section: Discussionsupporting
confidence: 68%
See 3 more Smart Citations